Impact of technical diagnostics interval on machinery maintenance - Mayer, Karel; Pexa, Martin; Pavlu, Jindrich (Manufacturing Technology Journal, 2012)
Machinery maintenance significantly participates in its reliable, serviceable and safe operation. Well-timed maintenance can identify a fault condition of machinery leading to manufacturing a product of poor quality. Maintenance interval can be fixed or maintenance can be done when needed, meaning at the moment when some of operating parameters get worse. An example of determination of diagnostics interval set based on machinery vibrodiagnostic measurement is described in the paper. The shown steps are universal and can be applied to another technical diagnostics methods as for example tribodiagnostics, thermodiagnostics, non-destructive materiology etc.. This way economic savings can be reached better comparing to maintenance done in fixed planned dates.
Keywords: maintenance; diagnostics interval; vibrodiagnostics